Costs and benefits of masting: economies of scale are not reduced by negative density‐dependence in seedling survival in Sorbus aucuparia. Issue 4 (17th December 2021) - Seget, Barbara; Bogdziewicz, Michał; Holeksa, Jan; Ledwoń, Mateusz; Milne‐Rostkowska, Fiona; Piechnik, Łukasz; Rzepczak, Alicja; Żywiec, Magdalena
Summary: Masting is a widespread reproductive strategy in plants that helps to reduce seed predation and increase pollination. However, masting can involve costs, notably negative density‐dependent (NDD) seedling survival caused by concentrating reproduction in intermittent events. Masting benefits have received widespread attention, but the costs are understudied, which precludes understanding why some plant species have evolved intense masting, while others reproduce regularly. We followed seed production, seed predation (both 13 yr), and seedling recruitment and survival (11 yr) in Sorbus aucuparia . We tested whether NDD in seedling survival after mast years can reduce the benefits of pulsed reproduction that come through predator satiation. Seed predation rates were extreme in our population (mean = 75%), but were reduced by masting. The commonly accepted, but untested, assertion that pulsed recruitment is associated with strong NDD was unsupported. Consequently, the proportion of seedlings that survived their first year increased with fruit production. This provides a rare test of economies of scale beyond the seed stage. Our results provide estimation of the costs of mast seeding, and indicate that these may be lower than expected. Low masting costs, if common, may help explain why masting is such a widespread reproductive strategy throughout the plant kingdom.